miR-409-3p represses Cited2 to refine neocortical layer V projection neuron identity - Wagner, Nikolaus R.; Sinha, Ashis; Siththanandan, Verl; Kowalchuk, Angelica M.; MacDonald, Jessica L.; Tharin, Suzanne (Frontiers in Neuroscience, 2022)
The evolutionary emergence of the corticospinal tract and corpus callosum are thought to underpin the expansion of complex motor and cognitive abilities in mammals. Molecular mechanisms regulating development of the neurons whose axons comprise these tracts, the corticospinal and callosal projection neurons, remain incompletely understood. Our previous work identified a genomic cluster of microRNAs (Mirg/12qF1) that is unique to placental mammals and specifically expressed by corticospinal neurons, and excluded from callosal projection neurons, during development. We found that one of these, miR-409-3p, can convert layer V callosal into corticospinal projection neurons, acting in part through repression of the transcriptional regulator Lmo4. Here we show that miR-409-3p also directly represses the transcriptional co-regulator Cited2, which is highly expressed by callosal projection neurons from the earliest stages of neurogenesis. Cited2 is highly expressed by intermediate progenitor cells (IPCs) in the embryonic neocortex while Mirg, which encodes miR-409-3p, is excluded from these progenitors. miR-409-3p gain-of-function (GOF) in IPCs results in a phenocopy of established Cited2 loss-of-function (LOF). At later developmental stages, both miR-409-3p GOF and Cited2 LOF promote the expression of corticospinal at the expense of callosal projection neuron markers in layer V. Taken together, this work identifies previously undescribed roles for miR-409-3p in controlling IPC numbers and for Cited2 in controlling callosal fate. Thus, miR-409-3p, possibly in cooperation with other Mirg/12qF1 miRNAs, represses Cited2 as part of the multifaceted regulation of the refinement of neuronal cell fate within layer V, combining molecular regulation at multiple levels in both progenitors and post-mitotic neurons.